Racial Differences in the Association Between Luminal Master Regulator Gene Expression Levels and Breast Cancer Survival - Byun, Jung S. (2020)
Compared with their European American (EA) counterparts, African American (AA) women are more likely to die from breast cancer in the United States. This disparity is greatest in hormone receptor-positive subtypes. Here we uncover biological factors underlying this disparity by comparing functional expression and prognostic significance of master transcriptional regulators of luminal differentiation.